2008
DOI: 10.1021/ac800567n
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized, Continuous-Flow Zone Electrophoresis

Abstract: A new method for performing continuous electrophoretic separation of complex mixtures in microscale devices is proposed. Unlike in free-flow electrophoresis devices, no mechanical pumping is required--both fluid transport and separation are driven electrokinetically. This gives the method great potential for on-a-chip integration in multistep analytical systems. The method enables us to collect fractionated sample and tenfold purification is possible. The model of the operation is presented and a detailed desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…Recent developments of this method include studies by Bowser and co-workers on the use of free flow electrophoresis in the separation of mitochondria and primary amines (56)(57)(58). Zalewski et al demonstrated synchronized, continuous flow zone electrophoresis on a microfluidic device for the first time (59). In this study, the hydrodynamic flow was driven electrokinetically in addition to the orthogonal separation field.…”
Section: Protein Profilingmentioning
confidence: 98%
“…Recent developments of this method include studies by Bowser and co-workers on the use of free flow electrophoresis in the separation of mitochondria and primary amines (56)(57)(58). Zalewski et al demonstrated synchronized, continuous flow zone electrophoresis on a microfluidic device for the first time (59). In this study, the hydrodynamic flow was driven electrokinetically in addition to the orthogonal separation field.…”
Section: Protein Profilingmentioning
confidence: 98%
“…Zalewski et al performed the first example of synchronized, continuous-flow zone electrophoresis on a microfluidic device [13]. This technique is also related to FFE, except that hydrodynamic flow, as well as separation, is electrokinetically driven.…”
Section: Ffementioning
confidence: 99%
“…Various processes, such as FFE, are well known on the preparative-scale, whereas others, such as IEF, have been well characterized for analytical-scale separations. There have been many innovative areas of development on the smaller scale, including taking advantage of hydrodynamic counterflow [6,7], different channel designs [8], and applying electric fields perpendicular to the flow of the sample [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…5 Pressure injection is required for the traditional μFFE separating process, due to the limitation of pressure driving, cumbersome equipments, fluid leak and inaccurate control of the flow rate, which will seriously affect the results of both the reproducibility and the accuracy. 6 The whole process is controlled by the liquid pipeline. That results in difficulties for the leak tightness of the glass-PDMS chip.…”
Section: Introductionmentioning
confidence: 99%